Spillovers from Euro Area and U.S. Credit and Demand Shocks: Comparing Emerging Europe on the Basis of a GVAR Model - Ludmila Fadejeva; Martin Feldkircher; Thomas Reininger (Oesterreichische Nationalbank (OeNB), 2015)
We examine the international effects of adverse loan supply and aggregate demand shocks originating in the euro area and the U.S.A. For that purpose, we use a global vector autoregressive (GVAR) model and isolate disturbances stemming from loan supply from those of four other macroeconomic shocks by means of sign restrictions. Our general results are as follows: Domestic and international responses of total credit and output to an adverse loan supply shock are substantial. They are more pronounced than the responses to an aggregate demand shock. Under both types of shocks, total credit decreases considerably more strongly than output in the long run, implying a reduction in financial deepening. This deleveraging process is particularly pronounced in the case of loan supply shocks. Taking a regional angle, Central-, Eastern- and Southeastern Europe (CESEE) and even considerably more the Commonwealth of Independent States (CIS) are the most strongly affected regions, and their total credit and output responses are stronger than in the country of shock origin. This is true for both types of structural shocks in the euro area and in the U.S.A. Last, historical decompositions of deviations from trend growth show that for the euro area developments, foreign shocks originating in the U.S.A., the UK and the CESEE and CIS regions feature most prominently, while for the U.S. developments, foreign shocks emanating from the euro area and China play a considerable role.
Keywords: 330; Kreditrationierung; Finanzkrise; Schock; USA; Gesamtwirtschaftliche Nachfrage; VAR-Modell; Europa